The first described darkling beetle of the tribe Metaclisini (Coleoptera: Tenebrionidae) from Eocene Baltic amber - Nabozhenko, Maxim V.; Mckellar, Ryan C.; Bukejs, Andris (Zootaxa, 2021)
The description of an extinct species of Metaclisa Jacquelin du Val, 1861 (Tenebrionidae) is presented. This genus and the tribe Metaclisini are recorded as fossils for the first time, from Eocene Baltic amber. The new species Metaclisa ottoi sp. nov. belongs to the subgenus Trichometaclisa subgen. nov. and differs from all other Metaclisini in possessing short, fine recumbent setation on the pronotum and elytra; in addition, the prosternal process in Metaclisa ottoi sp. nov. is roundly bent down and weakly projected behind the procoxae, which differs from extant species.